Dopamine: A Modulator of Circadian Rhythms in the Central Nervous System - Korshunov, Kirill S.; Blakemore, Laura J.; Trombley, Paul Q. (Frontiers in Cellular Neuroscience, 2017)
Abstract Circadian rhythms are daily rhythms that regulate many biological processes – from gene transcription to behavior – and a disruption of these rhythms can lead to a myriad of health risks. Circadian rhythms are entrained by light, and their 24-hour oscillation is maintained by a core molecular feedback loop composed of canonical circadian (“clock”) genes and proteins. Different modulators help to maintain the proper rhythmicity of these genes and proteins, and one emerging modulator is dopamine. Dopamine has been shown to have circadian-like activities in the retina, olfactory bulb, striatum, midbrain, and hypothalamus, where it regulates, and is regulated by, clock genes in some of these areas. Thus, it is likely that dopamine is essential to mechanisms that maintain proper rhythmicity of these five brain areas. This review discusses studies that showcase different dopaminergic mechanisms that may be involved with the regulation of these brain areas’ circadian rhythms. Mechanisms include how dopamine and dopamine receptor activity directly and indirectly influence clock genes and proteins, how dopamine’s interactions with gap junctions influence daily neuronal excitability, and how dopamine’s release and effects are gated by low- and high-pass filters. Because the dopamine neurons described in this review also release the inhibitory neurotransmitter GABA which influences clock protein expression in the retina, we discuss articles that explore how GABA may contribute to the actions of dopamine neurons on circadian rhythms. Finally, to understand how the loss of function of dopamine neurons could influence circadian rhythms, we review studies linking the neurodegenerative disease Parkinson’s Disease to disruptions of circadian rhythms in these five brain areas. The purpose of this review is to summarize growing evidence that dopamine is involved in regulating circadian rhythms, either directly or indirectly, in the brain areas discussed here. An appreciation of the growing evidence of dopamine’s influence on circadian rhythms may lead to new treatments including pharmacological agents directed at alleviating the various symptoms of circadian rhythm disruption.